Survival guide for traders : how to set up and organize your trading business - McDowell, Bennett, 1957- (Hoboken, N. J. : Wiley, 2012)
'The must-have guide for anyone considering entering the exciting world of trading from homeThe biggest stumbling block for people looking to launch their own trading businesses from home is a failure to understand the complexities of the'back office' operations needed to be successful. Survival Guide for Traders is here to help. Packed with strategies for building a successful home trading business, and featuring answers to questions most up-and-coming traders would never think to ask, Survival Guide for Traders is required reading for anyone who wants to start and sustain a trading business from home. Explains how to create a trading business plan, set up an office, implement a trading system, use margin, deal with legal and financial issues, and keep appropriate records Examines the opportunities and challenges of handling a home-based trading business Details the process of setting up and organizing your trading business Includes a comprehensive'Trading Business Plan Template' that you can customize Written by Bennett McDowell, a highly regarded trader and trainer of traders The book for anyone even thinking about entering the exciting world of trading, the Survival Guide for Traders offers practical solutions that anyone can use in order to build a lasting, thriving home trading business'--
Includes index.
Keywords: Electronic trading of securities; Online stockbrokers; Investments; Finance, Personal; Small business -- Management; Home-based businesses -- Management